Prevalence of occupational exposure to carcinogens among workers of Arabic, Chinese and Vietnamese ancestry in Australia - Boyle, T.; Carey, Renee; Glass, D.; Peters, S.; Fritschi, Lin; Reid, Alison (Wiley-Liss Inc., 2015)
Background: Although job-related diseases result in more deaths per year than job-related injuries, most research concerning ethnic minority workers has concerned accidents and injuries rather than disease-causing exposures such as carcinogens. Methods: We conducted a telephone-based cross-sectional survey to estimate the prevalence of occupational exposure to carcinogens among a sample of ethnic minority workers in Australia, and compared their exposure prevalence to that of a sample of the general Australian-born working population ('Australian workers'). Results: One-third of the ethnic minority workers were exposed to at least one carcinogen at work. The likelihood of exposure to carcinogens was not significantly different from that of Australian workers, although the likelihood of exposure to individual carcinogens varied by ethnicity. Conclusion: Knowing the prevalence of exposure to carcinogens in the workplace in different ethnic groups will allow better targeted and informed occupational health and safety measures to be implemented where necessary.